Assessing and reporting leaking of violent intent: Influences of perpetrator and witness characteristics - Tampe, Laura (European journal of criminology, 2023)
Because the police are reliant on laypersons to report announcements (leaking) of terrorist attacks, it is crucial to examine potential determinants for their assessment of the seriousness of leaking and the likelihood to report it. Members of the law enforcement authorities also need to decide which instances of leaking to prosecute further. We asked 392 laypersons and 188 police students to assess the seriousness and anticipated likelihood to report/prosecute leaking. Using a behavioral process tracing (BPT) task, we examined which further information they consider important for their decisions. We also assessed participant characteristics that may influence these decisions. Laypersons rated the seriousness of leaking higher than police students, but were less likely to report it to the police than police students were likely to have the leaking prosecuted. Both groups selected information about the potential perpetrator's criminal history, political attitude, and repetition of leaking most frequently. Accordingly, receiving information about the potential perpetrator's criminal past, right-wing attitude, and repetition of leaking in the BPT task was associated with increases in the seriousness ratings and the likelihood to report/prosecute leaking in both groups. Concerning the participants? characteristics, particularly fear of terrorism (and partly political attitude and news consumption) predicted both the seriousness ratings and the likelihood to report/prosecute leaking. In conclusion, characteristics of both the potential perpetrator and the participants drove the decisions. Thus, it seems important to provide more information about the concept of leaking and to emphasize its importance in preventing terrorist attacks in order to improve the likelihood to report/prosecute it. Additionally, the development of objective assessment criteria for the police seems essential in order to reduce the influence of witnesses' characteristics on these decisions.